ANALYSIS OF UNESA STUDENTS' PERCEPTIONS OF THE IMPLEMENTATION OF THE CORE TAX ADMINISTRATION SYSTEM (CTAS) IN INDONESIA IN 2025 - Alifia Putri Indryani; Nadine Diura Setyawan (Count : Journal of Accounting, Business and Management, 2024)
This research aims to identify the views of students at UNESA regarding the potential and challenges of the Core Tax Administration System (CTAS) in increasing tax compliance in Indonesia. This research is quantitative research that uses descriptive quantitative methods. In this research, the population used Surabaya State University students. The sample was obtained using the Slovin Formula and resulted in 101 respondents. The data collection method used was using a questionnaire and data analysis techniques using a Likert scale. Data were analyzed using descriptive statistical methods, validity tests, reliability tests, normality tests, and chi-square tests using Google Form and SPSS 26 media. The results of this research were that Surabaya State University (UNESA) students agreed with the implementation of the Core Tax Administration System (CTAS) in 2025 in Indonesia.